XLike: Cross-lingual Knowledge Extraction - Tadić, Marko (Array, 2014)
The goal of the XLike project is to develop technology to monitor and aggregate knowledge that is currently spread across mainstream and social media, and to enable cross-lingual services for publishers, media monitoring and business intelligence. The aim is to combine scientific insights from several scientific areas to contribute in the area of cross-lingual text understanding. By combining modern computational linguistics, machine translation, machine learning, text mining and semantic technologies we plan to deal with the following two key open research problems: (1) to extract and integrate formal knowledge from multilingual texts with cross-lingual knowledge bases, and ; (2) to adapt linguistic techniques and crowdsourcing to deal with irregularities in informal language used primarily in social media. The developed technology will be language-agnostic, while within the project we specifically address English, German, Spanish, Chinese as major world languages and Catalan, Slovenian and Croatian as minority languages.